Ablation of the inferior olive prevents H-reflex down-conditioning in rats. - Xiang Yang Chen; Wang, Yu; Yi Chen; Chen, Lu; Jonathan Wolpaw (Journal of neurophysiology, 2016)
We evaluated the role of the inferior olive (IO) in acquisition of the spinal cord plasticity that underlies H-reflex down-conditioning, a simple motor skill. The IO was chemically ablated before a 50-day exposure to an operant conditioning protocol that rewarded a smaller soleus H-reflex. In normal rats, down-conditioning succeeds (i.e., H-reflex size decreases at least 20%) in 80% of animals. Down-conditioning failed in every IO-ablated rat (P< 0.001 vs. normal rats). IO ablation itself had no long-term effect on H-reflex size. These results indicate that the IO is essential for acquisition of a down-conditioned H-reflex. With previous data, they support the hypothesis that IO and cortical inputs to cerebellum enable the cerebellum to guide sensorimotor cortex plasticity that produces and maintains the spinal cord plasticity that underlies the down-conditioned H-reflex. They help to further define H-reflex conditioning as a model for understanding motor learning and as a new approach to enhancing functional recovery after trauma or disease.
Keywords: Spinal Cord

Cortical stimulation causes long-term changes in H-reflexes and spinal motoneuron GABA receptors. - Wang, Yu; Yi Chen; Lu Chen; Jonathan Wolpaw; Xiang Yang Chen (Journal of neurophysiology, 2012)
The cortex gradually modifies the spinal cord during development, throughout later life, and in response to trauma or disease. The mechanisms of this essential function are not well understood. In this study, weak electrical stimulation of rat sensorimotor cortex increased the soleus H-reflex, increased the numbers and sizes of GABAergic spinal interneurons and GABAergic terminals on soleus motoneurons, and decreased GABA(A) and GABA(B) receptor labeling in these motoneurons. Several months after the stimulation ended the interneuron and terminal increases had disappeared, but the H-reflex increase and the receptor decreases remained. The changes in GABAergic terminals and GABA(B) receptors accurately predicted the changes in H-reflex size. The results reveal a new long-term dimension to cortical-spinal interactions and raise new therapeutic possibilities.
Keywords: Spinal Cord

H-reflex up-conditioning encourages recovery of EMG activity and H-reflexes after sciatic nerve transection and repair in rats. - Yi Chen; Wang, Yu; Lu Chen; Sun, Chenyou; English, Arthur W.; Jonathan Wolpaw; Xiang Yang Chen (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2010)
Operant conditioning of the spinal stretch reflex or its electrical analog, the H-reflex, produces spinal cord plasticity and can thereby affect motoneuron responses to primary afferent input. To explore whether this conditioning can affect the functional outcome after peripheral nerve injury, we assessed the effect of up-conditioning soleus (SOL) H-reflex on SOL and tibialis anterior (TA) function after sciatic nerve transection and repair. Sprague Dawley rats were implanted with EMG electrodes in SOL and TA and stimulating cuffs on the posterior tibial nerve. After control data collection, the sciatic nerve was transected and repaired and the rat was exposed for 120 d to continued control data collection (TC rats) or SOL H-reflex up-conditioning (TU rats). At the end of data collection, motoneurons that had reinnervated SOL and TA were labeled retrogradely. Putative primary afferent terminals [i.e., terminals containing vesicular glutamate transporter-1 (VGLUT1)] on SOL motoneurons were studied immunohistochemically. SOL (and probably TA) background EMG activity recovered faster in TU rats than in TC rats, and the final recovered SOL H-reflex was significantly larger in TU than in TC rats. TU and TC rats had significantly fewer labeled motoneurons and higher proportions of double-labeled motoneurons than untransected rats. VGLUT1 terminals were significantly more numerous on SOL motoneurons of TU than TC rats. Combined with the larger H-reflexes in TU rats, this anatomical finding supports the hypothesis that SOL H-reflex up-conditioning strengthened primary afferent reinnervation of SOL motoneurons. These results suggest that H-reflex up-conditioning may improve functional recovery after nerve injury and repair.
Keywords: conditioning; peripheral nerve; plasticity; Reflex; regeneration; Spinal Cord